Discurso de posesión del alcalde metropolitano de Medellín - Agosto 26 de 1982 - Uribe Vélez, Alvaro (Estudios de Derecho, 1982)
Discurso de posesión del alcalde metropolitano de Medellín - Agosto 26 de 1982